2005
DOI: 10.1002/jmv.20419
|View full text |Cite
|
Sign up to set email alerts
|

A 5‐year study of the prevalence and genetic diversity of human caliciviruses associated with sporadic cases of acute gastroenteritis in young children admitted to hospital in Melbourne, Australia (1998–2002)

Abstract: The prevalence and genetic diversity of human caliciviruses causing sporadic cases of acute gastroenteritis in young children hospitalized in a large pediatric hospital in Melbourne, Australia over 5 years (incorporating January 1998-December 2002) was studied by reverse transcription and sequence analysis of part of the polymerase gene. The overall prevalence of calicivirus infection in children aged <5 years during the 5 year study was 9.2% (113/1,233), with 95% of the strains belonging to the Norovirus gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
80
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(95 citation statements)
references
References 35 publications
14
80
1
Order By: Relevance
“…Norovirus genotype GII.4 has also been reported as the main norovirus genotype in sporadic cases of gastroenteritis in children [9,25,28]. In accordance with these previous reports, our results show that norovirus GGII.4 was predominantly detected in the faeces of children.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Norovirus genotype GII.4 has also been reported as the main norovirus genotype in sporadic cases of gastroenteritis in children [9,25,28]. In accordance with these previous reports, our results show that norovirus GGII.4 was predominantly detected in the faeces of children.…”
Section: Discussionsupporting
confidence: 92%
“…However, few studies have investigated prospectively the relative contributions of the different enteric viruses and bacteria in children admitted to hospital for gastroenteritis in developed countries. In accordance with our results, studies conducted in other developed countries in hospitalized children found a large predominance of viruses (56 to 70%) versus bacteria (4 to 17%) [25,26]. A large retrospective study conducted in Australia found the same ratio between viral and bacterial etiologies in children [27].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is consistent with the findings of other studies of sporadic cases of gastroenteritis in children 50,51,52,53 .…”
Section: V2 Efficiency Of Norovirus Real-time Rt-pcr Techniquesupporting
confidence: 93%
“…Norovirus GGI strains constitute a minor proportion of strains in most outbreak 38 studies 51,54,55,56 . Maslin et al found that among noroviruses, GII were predominant as it was previously shown in industrialized countries 57 .…”
Section: V2 Efficiency Of Norovirus Real-time Rt-pcr Techniquementioning
confidence: 99%